2017
DOI: 10.1007/s12298-017-0448-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatial distribution of genetic diversity and validation of Indian foxtail millet core collection

Abstract: Foxtail millet [ (L.) P. Beauv.] is an important small millet, grown as a short duration, drought tolerant crop across the world. This crop can be grown on wide ranges of soil conditions and has an immense potential for food and fodder in rainfed and arid regions of the India. In the present study, 31 primer pairs (27 SSR and 4 EST-SSR) were used to analyse the genetic diversity in 223 core collection accessions. Analysis resulted in detection of a total of 136 alleles with an average of 4.38 alleles per locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The PIC values and an average number of alleles per locus have shown a strong positive association with each other, which is following the earlier studies. Trends of increasing genetic diversity based on higher PIC values were also reported by earlier researchers (Ramya et al, 2015;Chander et al, 2017). The selected genotypes were grouped into two major clusters collected from different regions having tolerant, intermediate and sensitive response towards HS.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The PIC values and an average number of alleles per locus have shown a strong positive association with each other, which is following the earlier studies. Trends of increasing genetic diversity based on higher PIC values were also reported by earlier researchers (Ramya et al, 2015;Chander et al, 2017). The selected genotypes were grouped into two major clusters collected from different regions having tolerant, intermediate and sensitive response towards HS.…”
Section: Discussionsupporting
confidence: 68%
“…Trends of increasing genetic diversity based on higher PIC values were also reported by earlier researchers (Ramya et al ., 2015; Chander et al ., 2017). The selected genotypes were grouped into two major clusters collected from different regions having tolerant, intermediate and sensitive response towards HS.…”
Section: Discussionmentioning
confidence: 99%
“…Height is a trait that may be targeted by human selection during crop domestication and improvement, and there is significant variation in height in landrace varieties of foxtail millet, and within green foxtail accessions ( Li and Yang, 2008 ; Chander et al, 2017a , b ; Ghimire et al, 2018 ). Differences in height amongst landrace varieties may reflect both an ancestral increase in height took place as selection for losing unproductive tillers, followed by differentiation as farmers in different localities targeted height for a variety of reasons, including grain production and foraging.…”
Section: Genes Contributing To Domestication-related Traitsmentioning
confidence: 99%
“…Morphological characterization does not reliably portray the genetic relationships among the genotypes because of environmental interactions, unknown genetic control of the traits and inadequate sampling of the genome in terms of phenotype. Thus, for genetic diversity assessment, molecular markers offer considerable advantages over the morphological markers (Reddy et al, 2006;Chander et al, 2017;Ramesh et al, 2017). The diversity studies at molecular level in foxtail millet are very meagre and were mainly based on RFLP analysis (Fukunaga et al, 2002), using these markers they have concluded that the foxtail millet landrace belonging to China were more variable.…”
Section: Introductionmentioning
confidence: 99%
“…During our investigation also the co-dominant markers were not available; the analysis was done using ISSR and RAPDs. In last 4-5 years number of studies have been performed using SSR and EST-SSRs for genetic diversity analysis in foxtail millet ( Goron and Raizada, 2015, Ali et al, 2016, Wang et al, 2016, Andesen and Nepal, 2017, Chander et al, 2017.…”
Section: Introductionmentioning
confidence: 99%